The writing of where : graffiti and the production of writing spaces - Lesh, Charles N. (Syracuse University Press, 2022)
"The Writing of Where examines how graffiti writers in Boston write and rewrite various spaces within and across the city. Drawing on a four-year study with graffiti writers, this book explores how writing communities-particularly those marginalized by local processes of neoliberal space-produce public texts that at once challenge existing discourses of place and produce new, emergent writing spaces organized around alternative social principles"-- Provided by publisher
Keywords: Graffiti -- Social aspects -- Massachusetts -- Boston.; Graffiti artists -- Massachusetts -- Boston -- Social conditions.; Street art -- Social aspects -- Massachusetts -- Boston.; Graffiti artists.; Graffiti -- Aspect social -- Massachusetts -- Boston.; Graffiteurs -- Massachusetts -- Boston -- Conditions sociales.; Art dans la rue -- Aspect social -- Massachusetts -- Boston.; Graffiteurs.; graffiti artists.; LANGUAGE ARTS & DISCIPLINES / Rhetoric; Graffiti -- Social aspects; Street art -- Social aspects; Massachusetts -- Boston